¿QUIÉN PAGA LOS COSTOS DEL INCUMPLIMIENTO DE LAS SENTENCIAS DEL TRIBUNAL PERMANENTE DE REVISIÓN (MERCOSUR)? RESPONSABILIDAD DEL ESTADO POR VIOLACIÓN DEL DERECHO DE LA INTEGRACIÓN ( ) / WHO PAYS THE COSTS OF DEFAULT JUDGMENTS OF PERMANENT REVIEW... - Perotti, Alejandro Daniel (REVISTA QUAESTIO IURIS, 2011)
DOI: http://dx.doi.org/10.12957/rqi.2011.10195 Trabalho recebido e avaliado pelo Conselho executivo da Revista Quaestio Iuris Resumo O presente artigo busca comentar duas decisões do Tribunal Permanente de Revisão do MERCOSUR (TPR) tomadas no marco da controvérsia sobre a livre circulação de pneumáticos remodelados, controvérsia entre Uruguai contra Argentina, como assim também analisar algumas consequências que surgem desse assunto. Palavras-chave: Tribunal Permanente de Revisão do Mercosul. Livre circulação de pneumáticos remodelados. Uruguai. Argentina. Abstract This article seeks to comment two decisions of the Permanent Court of Review of MERCOSUR (TPR) taken in the context of the controversy about the free circulation of pneumatics refurbished, controversy between Uruguay against Argentina, as well also analyze some consequences that arise from this issue. Keywords: Permanent Court of Revision of Mercosur. Free circulation of pnematics refurbished. Uruguay. Argentina.